2012
DOI: 10.1111/j.1095-8339.2012.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Population history and seed dispersal in widespread Central AmericanBegoniaspecies (Begoniaceae) inferred from plastome-derived microsatellite markers

Abstract: Seven plastid microsatellite markers derived from plastome sequence data were used to study the population genetic structure in two widespread Begonia spp. from Central America. In B. nelumbiifolia, no variation was found at any locus. In contrast, significant haplotype diversity was found in B. heracleifolia (hT = 0.937, hS = 0.444, 39 haplotypes, mean of 3.3 haplotypes per population), and populations showed high absolute levels of genetic differentiation (G'ST = 0.829, D = 0.407). The distribution of haplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 78 publications
4
47
0
Order By: Relevance
“…Probably, because of the pioneer/nomadic behaviour of wild C. papaya, and its short life cycle, populations could have established and expanded rapidly after the Isthmus of Tehuantepec arose, erasing any sign of past genetic break. Another study has shown similar results; Twyford et al (2013) found low F CT values between populations east and west from the isthmus for Begonia heracleifolia, a neotropical lowland plant. In contrast, Gutiérrez-Rodr ıguez et al (2011) found a phylogeographical break at the Isthmus of Tehuantepec, with private haplotypes at either side of the isthmus for Palicourea padifolia, a cloud forest herb.…”
Section: Isthmus Of Tehuantepec and Pleistocene Refugia Hypothesissupporting
confidence: 54%
See 4 more Smart Citations
“…Probably, because of the pioneer/nomadic behaviour of wild C. papaya, and its short life cycle, populations could have established and expanded rapidly after the Isthmus of Tehuantepec arose, erasing any sign of past genetic break. Another study has shown similar results; Twyford et al (2013) found low F CT values between populations east and west from the isthmus for Begonia heracleifolia, a neotropical lowland plant. In contrast, Gutiérrez-Rodr ıguez et al (2011) found a phylogeographical break at the Isthmus of Tehuantepec, with private haplotypes at either side of the isthmus for Palicourea padifolia, a cloud forest herb.…”
Section: Isthmus Of Tehuantepec and Pleistocene Refugia Hypothesissupporting
confidence: 54%
“…For tropical lowland species like C. papaya, responses to historical climatic fluctuations may depend on species-specific adaptations, therefore making the identification of refugia for complex tropical species assemblages difficult (Poelchau and Hamrick, 2012). Generalizations about refugia may apply only for species with similar ecological preferences, rather than at broad taxonomic scales (Twyford et al, 2013).…”
Section: Isthmus Of Tehuantepec and Pleistocene Refugia Hypothesismentioning
confidence: 99%
See 3 more Smart Citations